The Concept of Religious Pluralism in The Qur’an: An Analysis of Maqashidi Exegesis in The Indonesian Context - Aftonur Rosyad; Eko Zulfikar (IAIN Ponorogo, 2022)
Within Indonesian context, religious pluralism has been a polemic among Islamic scholars. Some are not agreed because they assume all religions are equal. Whilst others are agreed with understanding religious pluralism as a form of respect and belief in other religions. This paper discusses the concept of religious pluralism in the Qur'an. By using the thematic method and the maqashidi interpretation approach in the Indonesian context, it is concluded that the Qur'an recognizes religious plurality and recommends committing good for non-Muslims as long as they do not interfere. In Indonesia, the concept of religious pluralism is a social fact that invariably exists and requires interfaith coexistence by maintaining the specific characteristics or teachings of each religion. Seven efforts have at least been made to address religious pluralism in Indonesia which are establishing brotherhood (ukhuwah), egalitarianism (al-musawah), the principles of justice (al-'adalah), the principles of tolerance (tasamuh), the principles of mutual respect, cooperation and friendship, the principles of peaceful co-existence, and wise-constructive-transformative dialogues.